Cak Nur on Politics: Indonesian Political Islam and the Role of Islamic Politics - Hamudy, Nurul Annisa; Hamudy, Moh Ilham A (Al-Risalah, 2020)
The Indonesian political elites tend to use Muslims for their personal interests, instead of making Islam as their moral guide in the political arena, despite Nurcholish Madjidâ€™s (Cak Nur) secularization is needed. For this reason, this research discusses the political ideals of Cak Nur, especially the idea of â€‹â€‹secularization in the midst of the current political Islam in Indonesia. Using a descriptive method, literature study, and a qualitative approach, the results of the study showed that Islam essentially is not merely a formal structure or composition and collection of laws of the state and government. Islam is the embodiment of tawá¸¥Ä«d. It is a spiritual force that can give birth to a soul that is á¸¥anÄ«f, inclusive, democratic, and respects societyâ€™s pluralism. Therefore, an understanding of more advanced Islamic teachings, such as Cak Nurâ€™s secularization concept which according to Cak Nur's does not lead to secularism; as well as the need for freedom of thought, an idea of â€‹â€‹progress, and openness to ideas are a necessity in Indonesia. As such Moslem should use a secular lens to view worldly matters that need rational and objective thinking, rather than using faith, Islamic law, Ê»aqÄ«da (creed), and Ê»ibÄda (worship) which are spiritual matters.